Recent trends in protein and peptide drug delivery systems - Gupta, Himanshu; Sharma, Aarti (Asian Journal of Pharmaceutics (AJP), 2014)
With the discovery of insulin in 1922, identification and commercialization of potential protein and peptide drugs have been increased. Since then, research and development to improve the means of delivering protein therapeutics to patients has begun. The research efforts have followed two basic pathways: One path focused on noninvasive means of delivering proteins to the body and the second path has been primarily aimed at increasing the biological half-life of the therapeutic molecules.The search for approaches that provide formulations that are stable, bioavailable, readily manufacturable, and acceptable to the patient, has led to major advances in the development of nasal and controlled release technology, applicable to every protein or peptide. In several limited cases, sustained delivery of peptides and proteins has employed the use of polymeric carriers. More successes have been achieved by chemical modification using amino acid substitutions, protein pegylation or glycosylation to improve the pharmacodynamic properties of certain macromolecules and various delivery systems have been developed like the prolease technology, nano-particulate and microparticulate delivery systems, and the mucoadhesive delivery of peptides. The needle and syringe remain the primary means of protein delivery. Major hurdles remain in order to overcome the combined natural barriers of drug permeability, drug stability, pharmacokinetics, and pharmacodynamics of protein therapeutics. In our present review we have tried to compile some recent advances in protein and peptide drug delivery systems.